Online TEFL certificates: Are they enough? - Jeanine Amy Edgar; Geoff Lautenbach (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study addresses the lack of research conducted on the design of Teaching English as a Foreign Language (TEFL) certification courses. It focuses primarily on how graduates of online TEFL courses perceived the design of the course and whether they felt prepared for the complexities of teaching abroad. The study highlights the TEFL graduates’ perceptions of the overall design of the online TEFL course while describing their perceived confidence to teach abroad upon completion of the online TEFL course. Findings were based on a qualitative inquiry that facilitated the study of the participants' lived experiences which allowed the researchers to gain a deeper understanding of their opinions and perspectives. The results of this study propose that the participant’s held both negative and positive opinions of their TEFL courses. The content of the TEFL courses was perceived as being simple to access, well-sequenced, and with a good pace. Communication during the course was also shown in a very positive light. Participants felt that the online TEFL staff replied quickly, and those course deadlines were flexible and accommodating. The participants also appreciated the support that they received from their peers. They did, however, feel that the feedback could have been more tailored to their specific needs and that more support should be available upon completion of the online TEFL course. A major finding is that the participants did not generally feel prepared for the complexities of teaching abroad. Their suggestions include improvement in the following areas; classroom management, specific content according to age, and the curriculum and culture they were to teach.